Bahasa Gaul Mandarin Pada Media Sosial 抖音 (Dǒu Yīn) Periode 2020 - Ragita Saraswati Kustiwi; Nanda Lailatul Qadriani; Tri Budianingsih (Universitas Al Azhar Indonesia, 2022)
Along with the development of increasingly sophisticated technology, the use of Internet slang has grown rapidly through social media platforms, one of them is social media 抖音(Dǒuyin). To solving communication problems and understand the developmental treasures of Mandarin, it is necessary to understand the meaning, factors, and impacts of Internet slang. This study uses the qualitative method. The data from this study were obtained from video based on the hashtag #2020抖音网络用语 and the hashtags of each Internet slang. The results of this study indicate that the 25 internet slang on social media Dǒu Yīn in the 2020 period was composed of 5 types, that is an old word with new meanings (52%), words or sentences with innovations (16%), homophonic (16%), absorption of foreign language (8%), and abbreviations (8%). In addition, the factors for the formation of internet slang, among them are creativity and the reality of social factors. The impact of the formation of internet slang can be seen from the positive and negative impacts.Keywords: Internet slang, popular language, social media, Dou Yin